Development of fuzzy neuron controllers for industrial applications - Soh, Cheong Boon. (2008)
Two distinctive approaches are studied in this report to design neuro-fuzzy control systems for industrial applications. The first is a direct neuro-fuzzy control approach where the control is completely determined by fuzzy inference, and it requires no model of the system under control. The second approach adopted is a neuro-fuzzy scheduling approach. Information on the system model (even though it might not be accurate) is used to design conventional controllers at various operating points.